ABBAS KIAROSTAMI, THE TASTE AND POETRY OF IRANIAN CINEMA: WITH A TASTE OF CHERRY, THE WIND WILL CARRY US AWAY - Filho, Bento Matias Gonzaga (Seven Editora, 2024)
Jean-Luc Godard’s statement that "Cinema begins with D. W. Griffith and ends with Abbas Kiarostami", demonstrates such importance and genius of the Iranian director Abbas Kiarostami. In this article we will reflect on Kiarostami’s filmic narrative and his poetic cinema of "unfinished" style, as he himself states: "whenever we have the opportunity to include scenes in which we can solicit the viewer’s imagination, we offer him the effective possibility of creating the film with us". Two great films, Taste of Cherry, from 1997, and The Wind Will Carry Us, from 1999, were chosen to come into focus in the discussion about how Kiarostami diligently seeks his truth as a human being in a perspective of poetic simplicity. DOI:https://doi.org/10.56238/sevened2024.037-099